From communities to genomes: a multifaceted approach to depict bacterial life in soils - Lopes, Lucas Dantas (2017)
Unraveling soil microbial ecology is essential for improving sustainable agricultural productivity. Community-based studies revolutionized this field in the last decades, but much is yet to be disclosed. This thesis proposed an approach to increase the resolution of such studies by combining 16S rDNA high-throughput sequencing and population genomics, aiming to further explore the differences pointed by community analyses, as well as to overcome the limitations of using operational taxonomic units (OTUs) as ecological entities, and to introduce the evolutionary thinking in microbial ecology. Our main goal was to understand the features that make bacteria able to colonize sugarcane rhizosphere or live saprophytically in bulk soil. Rhizosphere and bulk soil are contrasting habitats for microbial life as they are highly distinct in its physical, chemical and consequently biological characteristics. Our results indicated that sugarcane shapes the rhizosphere microbiome and metabolism of D-galacturonic acid is a key function for colonizing this niche. Among the taxa prevailing in the rhizosphere, Pseudomonas genus was targeted for a more detailed study considering its known attributes for plant growth promotion. Seventy-six fluorescent Pseudomonas spp. were isolated and submitted to whole genome sequencing (WGS). A comparative genomic analysis was performed between populations from rhizosphere and bulk soil. Phylogenetic analyses classified the isolates in the P. fluorescens (57) or P. putida (19) groups. Twelve putative new species and two new proposed P. fluorescens subgroups were found in the prospected tropical soil. Comparative genomics revealed that phosphatases or xylose-utilization genes were significantly enriched in the rhizosphere and bulk soil populations of the P. fluorescens group, respectively. D-galactonate catabolism was higher in the rhizosphere population of the P. putida group based on both genotypic and phenotypic results. Growth in D-xylose was further explored using genetic modified strains and confirmed that this sugar is more used by members of the bulk soil than the rhizosphere population of the P. fluorescens group, a pattern also observed in the bulk soil microbiome. In summary, these findings constitute a step forward in understanding the ecology of rhizosphere and bulk soil bacteria, by overcoming some limitations of community-based analyses and showing genomic differences between bacterial populations of these habitats.